2021
DOI: 10.2340/00015555-3845
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-induced Painful Skin (Sun Pain): A New Differential Diagnosis in Photodermatology

Abstract: Photodermatoses are characterized by the development of skin eruptions following exposure to ultraviolet radiation or visible light. We report here the clinical findings and results of laboratory investigations and phototesting of 6 patients who experience debilitating and excruciating pain after sun exposure (“sun pain”) in the absence of any skin eruption. Phototesting with sub-erythemal doses of ultraviolet A radiation triggered localized pain in 4 patients. At follow-up, 3 female patients were found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…In this study, AK and BC occupied 87.3% and 66.7% of head and neck SC respectively, which was close to previous studies 40,41 . These implied that AK and BCC might be more vulnerable to chronic UV exposure 34 . AK is acknowledged as a premalignant skin lesion that can evolve towards intraepidermal SCC, requiring prompt treatment 42,43 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, AK and BC occupied 87.3% and 66.7% of head and neck SC respectively, which was close to previous studies 40,41 . These implied that AK and BCC might be more vulnerable to chronic UV exposure 34 . AK is acknowledged as a premalignant skin lesion that can evolve towards intraepidermal SCC, requiring prompt treatment 42,43 .…”
Section: Discussionmentioning
confidence: 98%
“…Admittedly, multiple predisposing risks are involved in the etiology of skin malignancies 33 , and therefore SC vary vastly by geographical areas 4,34 . Outdoor workers are often exposed to high levels of UV radiation 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that, despite adequate knowledge about photoprotection measures and risk factors for developing skin cancer, people do not correctly apply these measures 28,29 . Moreover, people with skin cancer history, even after receiving appropriate education following diagnosis, continued to develop sunburn 30 and show suboptimal adherence to photoprotection measures 31 …”
Section: Discussionmentioning
confidence: 99%
“…It is common knowledge that the incidence of NMSC increases with age and depends on genetic disposition (skin type according to Fitzpatrick), UV exposure, and individual use of sun protection 29 . To counter this risk, we should offer our patients advice on the general preventative measures of UV protection (responsible handling of UV exposure, topical sunscreens, and textile sun protection) and strongly recommend the established oncological screening examinations (skin cancer screening) 30 …”
Section: Cancer Riskmentioning
confidence: 99%